Cytotoxic arylbenzofuran and stilbene derivatives from the twigs of Artocarpus heterophyllus - Sirada Boonyaketgoson (2018)
© 2017 Elsevier Ltd Four new natural products, including three arylbenzofurans named heterophyllenes A-C (1–3), and one stilbene named heterophyllene D (4), together with twenty-one known compounds were isolated from the twigs of Artocarpus heterophyllus and their structures elucidated by spectroscopic methods, mainly 1D and 2D NMR spectroscopy. The cytotoxic activity of selected compounds against KB, MCF-7 and NCI-H187 cell lines was evaluated. Heterophyllene C (3) exhibited cytotoxicity against the MCF-7 cell line with an IC 50 value of 12.56 μM. Additionally, the known compounds norartocarpin and artocarpin showed cytotoxic activity against MCF-7 and KB cell lines with IC 50 values of 10.04 and 13.57 μM, respectively. Both compounds also displayed cytotoxicity against the NCI-H187 cell line with values of 14.78 and 14.21 μM, respectively.